2019
DOI: 10.3389/fped.2019.00200
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic and Thoracoscopic Surgery: Prospective Series of 186 Pediatric Surgeries

Abstract: Objective: We present the applications and experiences of robot-assisted laparoscopic and thoracoscopic surgery (RALTS) in pediatric surgery. Materials and Methods: A prospective, observational, and longitudinal study was conducted from March 2015 to March 2018 that involved a non-random sample of a pediatric population that was treated with RALTS. The parameters examined were: gender, age, weight, height, diagnoses, surgical technique, elapsed time of console surgery, estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 79 publications
1
25
0
1
Order By: Relevance
“…Acquired anomalies, such as diaphragmatic paralysis, can also be resolved with RATS. The experience of other authors and ours confirms that robotic surgery is safe and effective for repairing diaphragm abnormalities in children [23,45] . Slater and Meehan [45] preferred the thoracic approach for repairing Bochdalek congenital diaphragmatic hernia, but sometimes smaller babies, less than 2.5 kg, can improve with the abdominal approach, since articulated instruments require considerable length to maneuver.…”
Section: Congenital Diaphragm Abnormalities Including Eventration Ansupporting
confidence: 82%
See 3 more Smart Citations
“…Acquired anomalies, such as diaphragmatic paralysis, can also be resolved with RATS. The experience of other authors and ours confirms that robotic surgery is safe and effective for repairing diaphragm abnormalities in children [23,45] . Slater and Meehan [45] preferred the thoracic approach for repairing Bochdalek congenital diaphragmatic hernia, but sometimes smaller babies, less than 2.5 kg, can improve with the abdominal approach, since articulated instruments require considerable length to maneuver.…”
Section: Congenital Diaphragm Abnormalities Including Eventration Ansupporting
confidence: 82%
“…However, many studies have reported that robotassisted surgery is safe and feasible for pediatric patients. RATS has previously been described as part of a series of general pediatric surgeries or a series of various thoracic pathologies [22,23,26,27] , a series of pediatric cases of specific procedures such as thymectomy for myasthenia gravis [28,29] , tracheopexy for treatment of severe tracheomalacia [30] , or as pediatric case reports on esophageal leiomyoma and bronchogenic cyst [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While robotics is widely applied in different fields, the medical use of this equipment has been on the rise. According to Arellano and González ( 1 ), robotics is used in urology and other medical disciplines ( 2 ). However, robotic training and simulation still trail to adopt this form of surgical technology.…”
Section: Introduction and Background To The Topicmentioning
confidence: 99%